2022
DOI: 10.1145/3491039
|View full text |Cite
|
Sign up to set email alerts
|

Using Personality Detection Tools for Software Engineering Research: How Far Can We Go?

Abstract: Assessing the personality of software engineers may help to match individual traits with the characteristics of development activities such as code review and testing, as well as support managers in team composition. However, self-assessment questionnaires are not a practical solution for collecting multiple observations on a large scale. Instead, automatic personality detection, while overcoming these limitations, is based on off-the-shelf solutions trained on non-technical corpora, which might not be readily… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 112 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…However, inferring the dimensions of Openness and Neuroticism through automated methods presents challenges, and existing studies have reported low accuracy in predicting personality traits ( Bai et al, 2013 ; Adalı & Golbeck, 2014 ). This challenging prediction holds in software engineering context ( Calefato et al, 2018a ; Calefato & Lanubile, 2022 ). The estimated correlation between self-reported and predicted personality traits is generally below 0.5 ( Novikov, Mararitsa & Nozdrachev, 2021 ).…”
Section: Background and State Of The Artmentioning
confidence: 99%
“…However, inferring the dimensions of Openness and Neuroticism through automated methods presents challenges, and existing studies have reported low accuracy in predicting personality traits ( Bai et al, 2013 ; Adalı & Golbeck, 2014 ). This challenging prediction holds in software engineering context ( Calefato et al, 2018a ; Calefato & Lanubile, 2022 ). The estimated correlation between self-reported and predicted personality traits is generally below 0.5 ( Novikov, Mararitsa & Nozdrachev, 2021 ).…”
Section: Background and State Of The Artmentioning
confidence: 99%